No Truth Without Beauty God, the Qur'an, and Women's Rights - El-Ali, Leena (Sustainable Development Goals Series, 2022)
In this comprehensive open access book, written for readers from any or no religious background, Leena El-Ali does something remarkable. Never before has anyone taken on every last claim relating to Islam and women and countered it not just with Qur'anic evidence to the contrary, but with easy-to-use tools available to all. How can a woman's testimony be worth half of a man's? How can men divorce their wives unilaterally by uttering three words? And what's with the obsession with virgins in Paradise? Find the chapter on any of the seventeen topics in this book, and you will quickly learn a) where the myth came from and b) how to bust it. The methodology pursued is simple. First, the Qur'an is given priority over all other literary or "scriptural" sources. Second, the meaning of its verses in the original Arabic is highlighted, in contrast to English translations and/or widespread misunderstanding or misinterpretation.